Odoribacter splanchnicus inhibits toxin production in Clostridioides difficile: insights from clinical correlation and in vitro validation - Wang, Na; Fan, Jing; Geng, Xianbo; Zhang, Shujuan; Pan, Zhaoyi; Jin, Changzhong; Chen, Yunbo; Wu, Nanping (Frontiers in Microbiology, 2026)
BackgroundClostridioides difficile infection (CDI) is a leading cause of healthcare-associated diarrhea. Although gut microbiota dysbiosis is central to CDI, the specific commensal species that confer protection are not well defined.MethodsWe performed 16S rRNA sequencing on fecal samples from a clinical cohort of 30 CDI patients, 30 non-CDI diarrhea patients, 27 asymptomatic C. difficile carriers, and 30 healthy controls. To functionally validate the clinical finding, an in vitro anaerobic co-culture system was established between the Odoribacter splanchnicus type strain and C. difficile. Toxin protein levels in the supernatant were quantified by ELISA at multiple time points (24, 48, and 72 h). Sporulation was assessed via ethanol resistance assays, and the expression of toxin genes (tcdA/tcdB) was measured by quantitative PCR (qPCR).ResultsClinical analysis revealed a significant negative correlation between the abundance of Odoribacter splanchnicus and CDI severity. In vitro, a high initial ratio of O. splanchnicus significantly suppressed C. difficile toxin production during the stationary phase, without inhibiting bacterial growth. This reduction in vitro levels was accompanied by a concurrent increase in sporulation and was preceded by a downregulation of tcdB gene expression.ConclusionThis work positions O. splanchnicus as a highly promising candidate for the development of next-generation, defined microbial therapeutics and provides a mechanistic foundation for future anti-virulence approaches to combat CDI.